Additively manufactured metasurfaces and metamaterials: Designs, fabrications, and applications from microwave to photonics - Meisam Esfandiari; Jianfeng Zhu; Yang Yang (APL Photonics)
Additive manufacturing (AM) or 3D printing wholly reinvents the making of metasurfaces/metamaterials and opens new opportunities from microwave to photonics. Conventionally, metasurfaces/metamaterials (engineered to control electromagnetic waves strongly) have been challenging and expensive to fabricate using traditional manufacturing techniques. However, AM provides an innovative turn in transforming the design and production of such complicated surfaces. It renders flexibility, efficiency, and economic viability to the fabrication process, enabling rapid prototyping and customization. This will, therefore, enable production times to be shorter, reduce material waste, and allow the creation of more complicated and much smaller metasurface structures than hitherto unattainable. Thus, AM drives strong advancements in microwave and photonic, enabling new applications and improved performance in telecommunications, wearable sensors, and imaging systems.